Perlindungan Hukum Terhadap Debitor Terhadap Penarikan Objek Jaminan Yang Masih Terikat Dalam Hubungan Perlindungan Angsuran Kreditur Debitur - Munsaf, Aidil; Suzanalisa, Suzanalisa; Fatriansyah, Fatriansyah (Universitas Batanghari Jambi, 2024)
Finance companies in providing financing credit to their consumers use a Fiduciary guarantee system. Legal protection for debtors upon withdrawal of fiduciary collateral objects following the constitutional court decision Number 2/PUU-XIX/2021 has been regulated in a preventive and repressive manner. Preventively, legal protection for debtors upon withdrawal of fiduciary collateral objects has been regulated in the provisions of the Fiduciary Guarantee Law which was then confirmed in the Regulation of the Minister of Finance of the Republic of Indonesia Number 130/PMK.010/2012. Apart from that, preventive protection is also emphasized in the Constitutional Court Decision Number 2/PUU-XIX/2021 in conjunction with the Constitutional Court Decision 18/PUU-XVII/2019. If the debtor objects to having his vehicle taken, the leasing party or debt collector may not take the vehicle by force. This vehicle may be taken if there has been a court decision with permanent legal force. What the public needs to know is that the way to enforce unlawful acts committed by consumers who are in arrears on motor vehicle loans is by applying for execution in court, not by being taken by force. as for how to deal with Finance business actors and Debt Collectors who carry out their work.